Analisis Usahatani Porang Sebagai Upaya Diversifikasi Pangan Di Masa Mendatang - Alevalia, Alevalia; Arvianti, Eri Yusnita (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Porang plant is a tuber plant that has great potential as a food ingredient in the context of food diversification. This potential has a positive impact on increasing the demand for porang. Porang farming must pay attention to land management, costs and farmers' income. The purpose of this study was to determine the amount of revenue on porang farming, to determine the income of porang farming, income and to determine the feasibility of porang farming by calculating the R/C ratio on porang farming. The research was conducted in Pait Village, Kasembon District, Malang Regency. The determination of respondent farmers was carried out using a purposive side technique, with several considerations, namely porang farmers in Pait Village, with five years of farming experience, the results obtained were 30 respondent farmers. The data collected is primary and secondary data with interview, observation and documentation techniques For data analysis used is farming analysis with the results of the average production cost of Rp 910,500, the average income of Rp 1,800,000, the average income of porang farmers is Rp 898,500 and the R/C ratio is 1.98. So the porang farming carried out by farmers in Pait Village is feasible.